P088: Emergency physicians' approach to head CT scanning for elderly patients who fall: A survey of Canadian, American, British, and Australian emergency physicians. (May 2019) - MacDonald, S.; Mercier, É.; O'Brien, T.; Mercuri, M.; de Wit, K.
Abstract : Introduction : The number of seniors presenting to emergency departments after a fall is increasing. Head injury concerns in this population often leads to a head CT scan. The CT rate among physicians is variable and the reasons for this are unknown. This study examined the role of patient characteristics and country of practice in the decision to order a CT.Methods : This study used a case-based survey of physicians across multiple countries. Each survey included 9 cases pertaining to an 82-year old man who falls. Each case varied in one aspect compared to a base case (aspirin, warfarin, or rivaroxaban use, occipital hematoma, amnesia, dementia, and fall with no head trauma). For each case, participants indicated how "likely" they were to order a head CT scan, measured on a 100-point scale. A response of 80 or more was defined a priori as 'likely to order a CT scan'. The survey was piloted among emergency residents for feedback on design and comprehension, and was published in French and English. Recruitment was through the Canadian Association of Emergency Physicians, Twitter and CanadiEM. For each case we compared the proportion of physicians who were 'likely to scan' with relative to the base case. We also compared the proportion of participants who were 'likely to scan' each case in the USA, UK and Australia, relative to Canada.Results : Data was collected from 484 respondents (Canada-308, USA-64, UK-67, Australia-27, and 18 from other countries). Social media distribution limited our ability to estimate of the response rate. Physicians were most likely to scan in the anticoagulation cases (90% likely to order a scan compared to 36% for the base case (p = <0.001)). Other features associated with increased scans were occipital hematoma (48%), multiple falls (68%), and amnesia (68%) (all p < 0.005). Compared to Canada, US physicians were more likely to order CT scans for all cases (p = <0.05). Compared to Canada, UK physicians were significantly less likely to order CT for patients in every case except in the patient with amnesia. Finally, Australian physicians differed from Canada only for the occipital hematoma case where they were significantly more likely to order CT scan.Conclusion : Anticoagulation, amnesia and a history of multiple falls appear to drive the ordering a head CT scan in elderly patients who had fallen. We observed variations in practice between countries. Future clinical decision rules will likely have variable impact on head CT scan rates depending on baseline practice variation.